Improving compliance with physical distancing across religious cultures in Israel - Gillie Gabay (BMC, 2021)
Abstract Background Physical distancing contains the corona virus, but compliance with physical distancing across religious minorities in Israel has been shown to be relatively poorer than in the majority population. This study tests the power of messages as drivers of willingness to comply with physical distancing across religious minorities in Israel during the first wave of the COVID-19 from March till June 2020. Methods 896 Israeli Muslims, Druze, Bedouins, Jewish Orthodox, Christians, and Jewish Seculars participated in this conjoint-based experimental design. The size of the total sample and of the subgroups is consistent with the suggested size in conjoint analysis studies, particularly when aiming at stability of coefficients rather than stability of means. The dependent variable was ‘willingness to comply’. Independent variables were known contributors to compliance: perceived risk, practices of physical distancing, ways to assure compliance, and the agent communicating the policy. Results A regression analysis indicated minor differences in the power of messages across groups despite dramatic cultural differences amongst them. We identified three distinct mindsets that transcend religious cultures from the responses of the study subjects to various messages and named them “pandemic observers,” “obedient followers,” and “sensitive interpreters.” Compliance of "Pandemic Observers" (n = 306) may be improved by messages such as, “Dangerous virus spreading wildly” and “Health experts suggest what to do but the government is reactive rather than proactive” (β = 14, p < .005). Compliance of "Obedient Followers" (n = 242) may be driven by the messages “Socialize and work only from home, using the internet, e.g. zoom/Skype” and “Everyone should stay 2 m. (6 ft.) apart” (β = 16, p < .0050). Compliance of "Sensitive Interpreters" (n = 249) may be improved by messages such as, “Only people who are 60 and over are to be allowed to buy groceries during first 2 h from opening” and by using the media to publicize the official health policy (β = 8; p < .005). Conclusions Mindset-assignment reflects how people think rather than their religious affiliation. A personal viewpoint identifier was developed to predict mindset-assignment and enable health authorities to enhance compliance through mindset-tailored messages for members of each mindset segment. We recommend that health authorities and policy makers consider these different personality types, which range across religious minorities and emphasize the messages that each type responds to in developing and implementing a communication plan to improve physical distancing as an important public health measure.